The Relationship between Shipment-Tracking and Timeliness of Delivery with Customer Satisfaction of Shopee Standard Express - Ngai Gui Shan,; Wan Ahmad, Wan Nurul Karimah (Research in Management of Technology and Business, 2025)
Green in the competitive e-commerce landscape, logistics performance is a critical determinant of customer satisfaction. This study examines the relationship between shipment tracking, timeliness of delivery, and customer satisfaction with Shopee Standard Express services in Johor, Malaysia. A quantitative approach was utilized, with 384 surveys distributed and 311 valid responses collected, achieving a response rate of 80.99%. The collected data were analyzed using statistical package for social sciences (SPSS) for the purpose of reliability and correlation, and descriptive analysis. The study showed that shipment tracking and timeliness of delivery are positively correlated with customer satisfaction. The survey identified shipment tracking has stronger relationship with factor in customer satisfaction, as respondents particularly valued features such as real-time data updates and clear visibility of their shipment status. Punctuality of delivery was also considered influential whereas delay in delivering assignments during the rush hour was cited as a concern. The mean scores for shipment tracking, timeliness of delivery, and customer satisfaction indicated that users had a positive perception of Shopee Standard Express services, particularly regarding transparency, reliability, and overall service quality. This study emphasizes the need for Shopee Standard Express to enhance tracking technologies, improve delivery networks, and address seasonal delays. By doing so, the company can strengthen customer loyalty, bolster its competitive position, and contribute to the sustainability of e-commerce logistics in Malaysia.